Oxidative stress and protection against it in bacteria - Olha Maslovska; Solomiia Komplikevych; Svitlana Hnatush (Біологічні студії, 2023)
Microorganisms are exposed to reactive oxygen species (ROS) that are formed in various ways, in particular, as a result of respiration or other intracellular processes, during metal-catalyzed Fenton reactions, as a result of the action of UV- and X-radiation, under the influence of some antimicrobial drugs, or during the host immune oxidative-burst response against infection agents. In this review, we take a look at the mechanisms of microbial cell damage, including damage of lipids and proteins. Lipid peroxidation (LPO) is one of the main molecular mechanisms involved in oxidative damage to cellular structures. A variety of products are formed during LPO reactions: alkoxyl radicals, peroxyl radicals, hydroperoxides, diene conjugates, carbonyl compounds, aldehyde adducts with biopolymers, alcohols, esters, etc. These products include cytotoxic and highly reactive compounds. Free radical reactions of protein damage occur via hydrogen atom abstraction from α-carbon or SH-, NH2-groups of aminoacids and electron abstraction from nucleophile centers of proteins resulting in the fragmentation of proteins, their denaturation and the formation of amino acid radicals. Bacteria show a significant adaptive potential to the influence of stress agents, including ROS. We summarized the data on bacterial antioxidant protection, ROS redox sensors, and regulators of bacterial cell response to ROS exposure, focusing on the features of anaerobic microorganisms, as their responses to the oxidative damage are the least studied, and many problems remain unsolved. This review contains information about changes in fatty acid composition of lipids of the plasma membrane to maintain the necessary fluidity, and, thus, counteract the effects of various stressing agents, including ROS. The main modifications of the fatty acid composition of lipids important for the regulation of membrane fluidity are described, in particular, via changes in the degree of lipid saturation, cis/trans isomerization, and synthesis of cyclopropane fatty acids.